2016
DOI: 10.1038/mt.2016.146
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of RNA-transfected CD20-specific Chimeric Antigen Receptor T Cells in Dogs with Spontaneous B Cell Lymphoma

Abstract: Preclinical murine models of chimeric antigen receptor (CAR) T cell therapy are widely applied, but are greatly limited by their inability to model the complex human tumor microenvironment and adequately predict safety and efficacy in patients. We therefore sought to develop a system that would enable us to evaluate CAR T cell therapies in dogs with spontaneous cancers. We developed an expansion methodology that yields large numbers of canine T cells from normal or lymphoma-diseased dogs. mRNA electroporation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 62 publications
2
100
1
Order By: Relevance
“…RNA transfection has also been used to deliver the CAR gene construct, resulting in transient CAR expression (because the CAR gene is not inserted into the genome of the T cells 50 ). Such transient CAR-expressing T cell products have only short-lived benefits in preclinical models, with no durable responses observed 51 . Finally, non-viral vector-based introduction of the CAR gene into the T cell genome has been successfully achieved using a transposon-transposase system 52,53 , and clinical trials using such products have been reported, with the data demonstrating the safety and feasibility of this approach and providing preliminary evidence of CAR T cell activity 54 .…”
Section: Wwwnaturecom/nrclinoncmentioning
confidence: 99%
“…RNA transfection has also been used to deliver the CAR gene construct, resulting in transient CAR expression (because the CAR gene is not inserted into the genome of the T cells 50 ). Such transient CAR-expressing T cell products have only short-lived benefits in preclinical models, with no durable responses observed 51 . Finally, non-viral vector-based introduction of the CAR gene into the T cell genome has been successfully achieved using a transposon-transposase system 52,53 , and clinical trials using such products have been reported, with the data demonstrating the safety and feasibility of this approach and providing preliminary evidence of CAR T cell activity 54 .…”
Section: Wwwnaturecom/nrclinoncmentioning
confidence: 99%
“…transiently expressed the mRNA for the T cell receptor CD3ζ and for the tumor necrosis factor receptor superfamily member TNFRSF9 (4-1BB) into autologous T cells; the authors observed the antitumor effects of mesothelin-specific CAR-T cells but observed no corresponding toxicity in patients with metastatic pancreatic cancer and malignant papillary mesothelioma. Furthermore, data from completed preclinical 81 and clinical 82 trials at the University of Pennsylvania confirmed the feasibility, safety, and preliminary effectiveness of this method.…”
Section: Application Of Car-t Therapy In Patients With Gastrointestinmentioning
confidence: 73%
“…In a first-ever canine study, Panjwani and colleagues (58) have reported successful mRNA electroporation of primary canine T cells to generate CAR T cells. In brief, a novel expansion methodology was developed that yields large numbers of canine T cells from normal or lymphomadiseased dogs.…”
Section: Preliminary Data In Dogsmentioning
confidence: 99%